EPIDEMIOLOGICAL AND CLINICAL CHARACTERISTICS, CAUSATIVE DRUGS, AND DIAGNOSTIC CHALLENGES OF FIXED DRUG ERUPTION IN ELDERLY PATIENTS: IS BULLOUS TYPE A MORE COMMON CLINICAL PHENOTYPE? - Goncagül Babuna Kobaner; Esen Özkaya (İstanbul Tıp Fakültesi Dergisi)
Objective: The present study aimed to evaluate the epidemiological and clinical features, causative drugs, and diagnostic challenges of Fixed drug eruption (FDE) in elderly patients. Material and Methods: In this single-center, retrospective, cross-sectional study, we evaluated data of all consecutive adult patients (aged >18 years) with an established diagnosis of FDE between 1996-2018 in our tertiary referral center in Turkey. Elderly patients who were aged ≥60 years at the time of diagnosis were allocated to the study. Results: Among 182 adult FDE patients, 14 (7.7%) patients (male/ female=1/1.8) were in the elderly group (mean age=66.1±6.9 years). Fix drug eruption was induced by intermittently taken drugs in all patients, 50% of whom had polypharmacy (concurrent use of ≥5 medications). Trimethoprim-sulfamethoxazole (42.9%) and non-steroidal anti-inflammatory drugs (35.7%) were the main causative drugs, while ornidazole was a remarkable novel FDE inducer since 2011. Fix drug eruption was mostly located on the trunk and extremities. Mucosal involvement was less frequent. Ten (71.4%) patients had bullous FDE (BFDE). There were no statistically significant differences between the gender and mean ages of the patients with and without BFDE. Conclusion: Our long-term experience demonstrated that FDE may also affect elderly patients. Most of the patients had BFDEraising the question of whether the bullous type is a more common clinical phenotype in these patients. Among the important diagnostic challenges of FDE in this age group, e.g., polypharmacy, multimorbidity, recall problems, cognitive disorders, frailty, and immunosenescence, BFDE should also be kept in mind as it may clinically mimic Stevens-Johnson syndrome/toxic epidermal necrolysis, and autoimmune bullous diseases.